Institutional pressures and the extent of cross-channel integration: the moderating effect of enterprise's capabilities. Issue 1 (18th May 2020) - Zhang, Guangling; Liu, Chenchen; Wang, Hui
Abstract : Purpose: Currently, the issues of cross-channel integration (CCI) have become the attentive focus. However, little research based on institutional theory details the drivers of and obstacles to adopt CCI strategy. Combined with resource-based view (RBV) and institutional theory, this thesis studies the effect of institutional pressures on the manufactures' extent of CCI, through exploring the moderating effects of firm's technology competence and relationship governance capabilities on the relationship between institutional pressures and the extent of CCI. Design/methodology/approach: The survey data of 249 valid research samples were obtained from Chinese manufacturing enterprises. Statistical software such as SPSS 22.0 and AMOS 18.0 was used to analyze the data and test the conceptual model and relevant research hypotheses from an empirical perspective. Findings: The results of empirical study from 249 manufacturers indicate that the mimetic, coercive and normative pressures perceived by enterprises can significantly promote their extent of CCI; relationship governance capabilities attenuate the positive impact of mimetic pressures on the extent of CCI, but strengthen that of normative pressures on the extent of CCI; besides, technology competence can attenuate the positive effect of mimetic pressures on the extent of CCI, but enhance that of normative pressures on the extent of CCI. Originality/value: Few studied the impact of the interaction of internal capabilities and external institutional pressures on CCI of enterprises. This study combines institutional theory and resource-based view to fill the theoretical gap in this regard.